Technology radicalness and buyer-supplier knowledge management : implication to the implementation performance. - Abd. Rahman, Azmawani (2009)
If the breath and depth of the technology being acquired is beyond the capability of the adopting firms, the new technology is more likely to fail as early as at the implementation stage. The paper describes the important role of knowledge in the process of manufacturing technology adoption and implementation. Emphasis is given to the interaction between technology radicalness (TR), buyer-supplier knowledge management (BSKM), and implementation performance (IP). Although knowledge management has been widely discussed by many academicians and practitioners, there is a gap in the literature and lack of research on knowledge within the context of buyer supplier relationships in the process of technology adoption and implementation. Using a sample of the Malaysian manufacturing industry, the result of the study indicates that effective buyer-supplier knowledge management can enhance implementation performance, although the technology being implemented is radical to the acquiring firm.